Evaluation of Analgesic activity of Sterculia villosa Roxb. (Sterculiaceae) Bark in Swiss-Albino mice - Hossain, Md Monir; Even, ASM Ibnul Hasan; Akbar, Mohammad Ahsanul; Ganguly, Amlan; Rahman, SM Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2014)
The methanolic crude extract and different fractions of Sterculia villosa bark were investigated for their possible analgesic activity in experimental animal models. Analgesic activity was evaluated using acetic acid induced writhing inhibition and radiant heat tail-flick methods in swiss albino mice. In peripheral method of antinociception, the methanolic crude extract (400 mg/kg) and petroleum ether fraction (400 mg/kg) showed significant analgesic activity having 50.76% and 51.72% (P < 0.001) of writhing inhibition, respectively compared to standard aspirin (71.03% inhibition). In the radiant heat tail-flick method of central anti-nociception, the methanolic crude extract (400 mg/kg) and petroleum ether fraction (400 mg/kg) of S. villosa showed significant analgesic activity having 71.25% (P < 0.001) and 66.77% (P < 0.001) elongation of reaction time, respectively at 30 minutes after administration of sample compared to the standard morphine (144.4% elongation). The findings of the studies demonstrated analgesic activity of the bark of S. villosa which could be the therapeutic option against pain. Dhaka Univ. J. Pharm. Sci. 12(2): 125-129, 2013 (December) DOI: http://dx.doi.org/10.3329/dujps.v12i2.17622